Learning Management System–Supported Project-Based Learning and Its Effect on Students' Critical Thinking Disposition - Wisnu Djatmiko; Arum Setyowati; Sri Wahyuni (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2026)
technology-mediated instructional design in higher education, enabling flexible learning environments that integrate student-centered pedagogical approaches. Project-Based Learning (PjBL), when supported by LMS platforms, has the potential to enhance higher-order thinking; however, empirical evidence regarding its effectiveness in developing students’ critical thinking disposition remains limited. This study aims to examine the effect of LMS-supported Project-Based Learning on students’ critical thinking disposition within a flexible learning environment. A quasi-experimental method with a one-group pretest–posttest design was employed involving 93 undergraduate students enrolled in three core courses in the Electronic Engineering Education Study Program at Universitas Negeri Jakarta during the 2024/2025 academic year. Critical thinking disposition was measured using a validated instrument covering seven dispositional dimensions. Data were analyzed using paired sample t-test and N-Gain index. The results indicate a statistically significant improvement in overall critical thinking disposition scores (t = 4.57; p < 0.05); however, the N-Gain value (0.09) suggests low practical effectiveness. Improvements were more prominent in procedural dimensions such as analyticity and systematicity, while epistemic dimensions showed limited development. These findings highlight that LMS-supported Project-Based Learning contributes to procedural aspects of critical thinking disposition but requires complementary instructional design strategies emphasizing reflective dialogue, argumentation, and epistemic engagement to achieve deeper dispositional development. This study contributes to educational technology research by demonstrating the importance of aligning technological tools with pedagogical design to maximize the effectiveness of LMS-supported learning environments.